Sosialisasi Pentingnya Pengawasan Masyarakat dalam Pengelolaan Dana Desa di Desa Belabaja Kecamatan Nagawutung Kabupaten Lembata - Antonela Anggreni Goan; Agustina Beo Meo; Christian E.N. Sawa; Stephanie Perdana Ayu Lawalu; Indriyati Indriyati; Yasinta Yunrianto Palan Peten (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This community service project sought to investigate the significance of community oversight in village fund management, focusing on Belabaja Village. Socialization and observational activities revealed a low level of community participation in monitoring the management of village funds. Factors contributing to this low participation include limited public awareness, inadequate socialization efforts by the village government, community members' busy schedules, and a lack of strong relationships between village officials and the community. Despite these challenges, community oversight remains essential for ensuring transparency and accountability in the utilization of village funds. The study concludes that there is a need to enhance public awareness of the importance of oversight and to foster stronger partnerships between village governments and the community to achieve sustainable development objectives.